Engineered exosomes in emerging cell-free therapy - Si, Chaohua; Gao, Jianen; Ma, Xu (Frontiers in Oncology, 2024)
The discovery and use of exosomes ushered in a new era of cell-free therapy. Exosomes are a subgroup of extracellular vesicles that show great potential in disease treatment. Engineered exosomes. with their improved functions have attracted intense interests of their application in translational medicine research. However, the technology of engineering exosomes still faces many challenges which have been the great limitation for their clinical application. This review summarizes the current status of research on engineered exosomes and the difficulties encountered in recent years, with a view to providing new approaches and ideas for future exosome modification and new drug development.